1923 Conn. Pub. Acts 3708 - (:unkn) unknown (My University, 1923)
An Act Concerning the Possession, Sale and Use of Pistols and Revolvers, ch. 252, § 7: Prohibited the sale, delivery, or transfer of any pistol or revolver to any noncitizen.
Keywords: TRANSFER - DANGEROUS PERSONS